Modulation of Immunity by Antiangiogenic Molecules in Cancer - Magali Terme; Orianne Colussi; Elie Marcheteau; Corinne Tanchot; Eric Tartour; Julien Taieb (Clinical and Developmental Immunology)
In the last decades a new class of therapeutic drugs have been developed that block tumor angiogenesis. These antiangiogenic molecules, which target VEGF or VEGFR, PDGFR, and c-kit, can act not only on endothelial cells but also on immune cells. Some antiangiogenic molecules inhibit the development of immunosuppressive mechanisms developed by the tumors to escape the immune system (such as regulatory T cells, myeloid-derived suppressor cells, and immunosuppressive cytokines). These immunomodulatory effects must be characterized in detail to enable a better prescription of these treatments. In this paper we will focus on the impact of anti-angiogenic drugs on immunosuppression and their potential combination with immunotherapeutic strategies. Interestingly, immune parameters or their modulation during treatment could serve as potential biomarkers of response or resistance to anti-angiogenic therapies.